HUBUNGAN GAYA BELAJAR TERHADAP NILAI UJIAN BLOK MAHASISWA PSKPS FKIK ULM ANGKATAN 2020 - Aroya, Yovanka; Nurikhwan, Pandji Winata; Illiandri, Oski (Homeostasis, 2024)
Abstract: Block exams are held at the end of each block with the aim of evaluating learning outcomes. Learning style is one of the factors that influences a person's learning outcomes. This research aims to determine the correlation between learning styles and the block exam scores of PSKPS FKIK ULM students class of 2020. This research uses observational analysis methods and a cross-sectional design. Subjects in the study were selected using a total sampling technique according to the research exclusion and inclusion criteria. Primary data was taken using the VARK questionnaire and secondary data was obtained from students' block exam scores. The data analysis used was the chi-square test. The results of the study showed that the block value for complaints related to the musculoskeletal system was 27%, for the block for complaints related to the hemopoietic and lymphoreticular systems it was 48%, and for the block complaints related to the urogenital system was 35.5%. The majority of students study using a multimodal learning style as much as 69.7%, while 30.3% use a unimodal learning style. From the results of the bivariate analysis, it was found that the p-value was > 0.05, so it was concluded that there was no correlation between learning style and the block exam scores of PSKPS FKIK students at Lambung Mangkurat University class of 2020. Keywords: learning style, VARK, block exam. Abstrak: Ujian blok diadakan di setiap akhir dari sebuah blok dengan tujuan evaluasi hasil belajar. Gaya belajar merupakan salah satu faktor yang berpengaruh pada hasil belajar seseorang. Pada penelitian ini memiliki tujuan mengetahui hubungan gaya belajar dengan nilai ujian blok mahasiswa PSKPS FKIK ULM angkatan 2020. Penelitian ini menggunakan metode analisis observasi dan desain cross-sectional. Subjek pada penelitian dipilih melalui teknik total sampling sesuai kriteria eksklusi dan inklusi penelitian. Data primer diambil menggunakan kuesioner the VARK dan data sekunder didapat dari nilai ujian blok mahasiswa. Analisis data yang digunakan adalah uji chi-square. Hasil penelitian menunjukkan hasil nilai Blok Keluhan Berkaitan dengan Sistem Muskuloskeletal adalah 27%, pada Blok Keluhan Berkaitan dengan Sistem Hemopoetik dan Limforetikuler adalah 48%, dan Blok Keluhan Berkaitan dengan Sistem Urogenital adalah 35,5%. Mahasiswa belajar mayoritas menggunakan gaya belajar multimodal sebanyak 69,7%, sementara gaya belajar unimodal sebanyak 30,3%. Dari hasil analisis bivariat didapatkan p-value > 0,05, sehingga disimpulkan tidak ada hubungan antara gaya belajar terhadap nilai ujian blok mahasiswa PSKPS FKIK Universitas Lambung Mangkurat angkatan 2020. Kata-kata kunci: gaya belajar, VARK, ujian blok